TRANSLATION STRATEGIES OF SLANG WORDS IN THE SUBTITLE OF VENOM: LET THERE BE CARNAGE - Subhiya, Letifa Qothrunnada; Afriano, Reno (Universitas Gunadarma, 2024)
This study aims to identify the types of slang words and the translation strategies used to translate the slang words in Venom: Let There Be Carnage movie. Data collected by referring to the official movie transcripts in English and their translations in Indonesian, especially those that have been classified as slang words. To classify the slang, the researcher used the theory of types of slang by Allan and Burridge (2006), while the analysis process used the theory of translation strategies proposed by Baker (1992). The study found four out of five types of slang words, and the type “fresh and creative” mostly appeared with 17 data. It is followed by flippant which occurred 15 times, imitative 9 times, and clipping 4 times. Furthermore, the study also found seven out of eight translation strategies to translate the slang, and the most frequently used strategy is translation by a more general word which constitutes 46.6% of the total data. Meanwhile, the translation by illustration is not used. And the least strategy used to translate the slang words is translation using loan word or loan word with explanation with a total of 2.2%. Based on the findings, fresh and creative slang appears most frequently due to the casual atmosphere of the scenes, while acronyms are absent as they are more suitable for written text. The general word strategy is common due to the abundance of general terms, whereas the illustration strategy is rarely used due to spatial constraints in presenting additional visuals in scenes. Hopefully, this study can provide practical insights for translating similar movies.